Prostate cancers detected on repeat prostate biopsies show spatial distributions that differ from those detected on the initial biopsies. (17th April 2015) - Eminaga, Okyaz; Hinkelammert, Reemt; Abbas, Mahmoud; Titze, Ulf; Eltze, Elke; Bettendorf, Olaf; Wötzel, Fabian; Bögemann, Martin; Semjonow, Axel
<x xml:space="preserve">Abstract</x> Objective To evaluate the spatial distribution of prostate cancer detected at a single positive biopsy (PBx) and a repeat PBx (rPBx). Patients and Methods We evaluated 533 consecutive men diagnosed with prostate cancer who underwent radical prostatectomy using a clinical map document based on XML (cMDX©)‐based map model of the prostate. We determined the number of cancer foci, relative tumour volume, Gleason score, zone of origin, localisation, and pathological stage after stratification according to the number of PBx sessions (PBx vs rPBx). The distribution of 3966 prostate cancer foci was analysed and visualised on heat maps. The colour gradient of the heat map was reduced to six colours representing the frequency classification of prostate cancer using an image posterisation effect. Additionally, the spatial distribution of organ‐confined prostate cancer between PBx and rPBx was evaluated. Results Prostate cancer diagnosed on PBx was mostly localised to the apical portion and the peripheral zone of the prostate. Prostate cancer diagnosed on rPBx was more frequently found in the anterior portion and the base of the prostate. Organ‐confined prostate cancer foci were mostly localised in the dorsolateral zone of the prostate in men at PBx, whereas men at rPBx had more prostate cancer foci in the anterior portion. Conclusions The spatial distribution of prostate cancer with rPBx differs significantly from the spatial distribution of prostate cancer with PBx. The whole anterior portion of the prostate should be considered by rPBx.